Determining the effect of modified additives on the fire-extinguishing properties of compressed air foam - Shakhov, Stanislav; Vynohradov, Stanislav; Hryschenko, Dmytry; Savchenko, Alexander; Grinchenko, Evgen; Knaub, Liudmyla; Maslich, Nataliia; Mohylianets, Tetiana; Shevchuk, Viktor; Dominik, Andrij (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the fire extinguishing efficiency of compressed air foam with the use of modified additives. The main hypothesis assumes that the use of modified additives in the composition of the compressed air foam will affect its fire extinguishing efficiency when extinguishing solid combustible materials. The task addressed is to determine the effect of modified additives in compressed air foam with a concentration range of 1–5 % on its fire extinguishing properties. The results show that for all additives, when the concentration changes from 1 % to 5 %, characteristic is a slight decrease in the consumption of an aqueous solution of the foaming agent. On the contrary, an increase in the expansion ratio results in a significant decrease in the mass of the aqueous solution of the foaming agent consumed for extinguishing. An increase in the concentration of the additive in the range of 1 % to 3 % is characterized by a decrease in the extinguishing time, while a further increase from 3 % to 5 % is characterized by an increase in the extinguishing time. Also, the increase in the foam expansion ratio has a significant effect; with an increase from 5 to 20, a decrease in the extinguishing time is observed, and with a further increase to 25, an increase in time occurs. For the compressed air foam with NH4H2PO4, the highest efficiency index is Ie.e≈20.15 m2/l∙s, at a modified additive concentration of C≈3 % and a foam expansion ratio of K≈18; for the compressed air foam with (NH4)2HPO4, the highest efficiency index is Ie.e=18.04 m2/l∙s, at a modified additive concentration of C≈3 % and a foam expansion ratio of K≈18; for a compression foam with (NH4)2CO3, the highest efficiency index is Ie.e=14.99 m2/l∙s, at a modified additive concentration C≈3 % and a foam expansion ratio of K≈18. Thus, based on the results of experimental studies, the most effective is the compressed air foam with NH4H2PO4. The resulting extinguishing efficiency is 11 % higher than that of the compressed air foam with (NH4)2HPO4, and 26 % higher than that of the compressed air foam with (NH4)2CO3